Upaya Meningkatkan Kecerdasan Spiritual Siswa Melalui Program Full Day School di Madrasah Ibtidaiyah Kota Jombang - Effiana Cahya Ningrum; Nur Hidayat (Jurnal Penelitian, 2022)
The problem that occurs in MI students in Jombang City is the lack of spiritual intelligence of students as evidenced by the decline in children's manners and moral ethics. This is because students see negative videos that are spread on social media. So this study aims to find out how the full day school program implemented by Madrasah Ibtidaiyah (MI) in Jombang City can improve the spiritual intelligence of grade II students. Interviews and documentation are used as data collection methods in qualitative descriptive research methods. 27 students from class II were interested, the chairman, class II teacher, and the students as resource persons. The research method used is descriptive qualitative, with data collection techniques through interviews and documentation. 27 students from class II participated, the principal, class II teacher, and students' parents as informants. The results of the study showed that full-day learning was carried out at MI Jombang city from Monday to Friday from 06.55 to 15.40 WIB. There are many efforts to improve students' spiritual intelligence, including teachers delivering subject matter, congregational prayers, dhuha prayers, morning recitation, and the habit of one day one coin. Because through these habits students experience changes in attitudes such as discipline, having empathy for others, and always remembering Allah in their actions. However, these efforts can be further developed through positive activities so that students' spiritual intelligence can develop properly.